Marriage and Divorce Decline during the COVID-19 Pandemic: A Case Study of Five States - Manning, Wendy D. (Socius, 2021)
The decline in marriage and divorce was evident prior to the coronavirus disease 2019 pandemic, but it remains unknown whether these patterns have persisted during the pandemic. The authors compared monthly marriage and divorce counts for two years prior to the pandemic (2018 and 2019) and during the pandemic for the five states that published monthly vital statistics data for 2020 (Arizona, Florida, Missouri, New Hampshire, and Oregon). All five states witnessed initial declines in marriage. Counts of marriages in Arizona and New Hampshire rebounded. In contrast, marriage shortfalls occurred in Florida, Missouri, and Oregon. In the early pandemic months, divorces initially declined in all five states and rebounded in Arizona. In the remaining four states, divorce shortfalls have occurred. As more data become available, it will be important to acknowledge these state variations in response to the pandemic.